Exploring Interactions between Primary Hepatocytes and Non-Parenchymal Cells on Physiological and Pathological Liver Stiffness - Vaishaali Natarajan; Youra Moeun; Srivatsan Kidambi (Biology, 2021)
Chronic liver disease is characterized by progressive hepatic fibrosis leading to the formation of cirrhosis irrespective of the etiology with no effective treatment currently available. Liver stiffness (LS) is currently the best clinical predictor of this fibrosis progression irrespective of the etiology. LS and hepatocytes-nonparenchymal cells (NPC) interactions are two variables known to be important in regulating hepatic function during liver fibrosis, but little is known about the interplay of these cues. Here, we use polydimethyl siloxane (PDMS) based substrates with tunable mechanical properties to study how cell–cell interaction and stiffness regulates hepatocytes function. Specifically, primary rat hepatocytes were cocultured with NIH-3T3 fibroblasts on soft (2 kPa) and stiff substrates that recreates physiologic (2 kPa) and cirrhotic liver stiffness (55 kPa). Urea synthesis by primary hepatocytes depended on the presence of fibroblast and was independent of the substrate stiffness. However, albumin synthesis and Cytochrome P450 enzyme activity increased in hepatocytes on soft substrates and when in coculture with a fibroblast. Western blot analysis of hepatic markers, E-cadherin, confirmed that hepatocytes on soft substrates in coculture promoted better maintenance of the hepatic phenotype. These findings indicate the role of stiffness in regulating the hepatocytes interactions with NPCs necessary for maintenance of hepatocytes function.